2021
DOI: 10.1111/jvim.16199
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, diagnosis, and survival analysis of dogs with glioma

Abstract: Background: Gliomas in dogs remain poorly understood.Objectives: To characterize the clinicopathologic findings, diagnostic imaging features and survival of a large sample of dogs with glioma using the Comparative Brain Tumor Consortium diagnostic classification.Animals: Ninety-one dogs with histopathological diagnosis of glioma.Methods: Multicentric retrospective case series. Signalment, clinicopathologic findings, diagnostic imaging characteristics, treatment, and outcome were used. Tumors were reclassified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
141
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(158 citation statements)
references
References 71 publications
(246 reference statements)
12
141
2
3
Order By: Relevance
“…Leptomeningeal spread is a clinically relevant and possibly devastating finding, with implications for treatment options and prognosis in humans 6,7,14 . Leptomeningeal spread of choroid plexus carcinomas and glial tumours has been described in dogs 12,15,16 . Usually, metastasis or spread occurs in the direction of CSF flow, which is mostly caudal.…”
Section: Discussionmentioning
confidence: 99%
“…Leptomeningeal spread is a clinically relevant and possibly devastating finding, with implications for treatment options and prognosis in humans 6,7,14 . Leptomeningeal spread of choroid plexus carcinomas and glial tumours has been described in dogs 12,15,16 . Usually, metastasis or spread occurs in the direction of CSF flow, which is mostly caudal.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the available data in dogs show a poor prognosis with eventually death or euthanasia as a direct result of the severity of the clinical signs. The reported mean survival time for dogs with intracranial gliomas was 84 days despite treatment with surgery or RT, although RT appears to enhance the survival time as a single treatment or after surgery 7,9,13,29 . One prospective study revealed that the medium survival time in 51 dogs with infratentorial tumours was no longer than 2 months when treated with palliative treatment (prednisolone and/or anti‐epileptic medication) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The reported mean survival time for dogs with intracranial gliomas was 84 days despite treatment with surgery or RT, although RT appears to enhance the survival time as a single treatment or after surgery. 7,9,13,29 One prospective study revealed that the medium survival time in 51 dogs with infratentorial tumours was no longer than 2 months when treated with palliative treatment (prednisolone and/or anti-epileptic medication). 30 In our case, a combination of a total radiation dose of 50 Gy and oral glucocorticoids resulted in a survival time of half a year from when treatment was started.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations